Examination of the conventional assumption of internal equilibrium within the states of a biochemical cycle. - Hill, T L (1980)
If k is a representative "internal" rate constant between substates of a given biochemical state, and if alpha is representative of the rate constants of the biochemical cycle to which the state belongs, then cyclical activity at steady state pulls the substates out of internal equilibrium with each other by a factor of order 1 +/- O(alpha/k). For transients or steady isotonic contractions in muscle, the departures from internal equilibrium can be larger than this. The simplifying assumption that internal equilibrium is always maintained between the substates is justified at steady state, as a good approximation, if k/alpha greater than or equal to 100. In muscle contraction at maximum velocity, something like k/alpha greater than or equal to 500 is required. This problem is superficially similar to the question, in Eyring's rate theory, of the extent to which activated complex leads to products pulls the activated complex out of the assumed equilibrium with reactants.